TikTok Social Media: A Breakthrough to the Moderation in Da’wah Education - Muhamad Basyrul Muvid; Didiet Anindita Arnandy; Achmad Arrosyidi (STAI Hubbulwathan Duri, 2024)
TikTok as a social media, nowadays is increasingly used for various purposes including video content about religion, such as Da’wah. It is an effective choice to disseminate moderate da'wah for the process of educating (tarbiyah) the community to become smart, wise, and polite people who can implement their spiritual and social responsibilities. The research method in this study used a qualitative type using a literature study approach, with data collection techniques of documentation on TikTok videos, and data analysis techniques using induction, interpretation, and comparison. The results of this study show that the moderation in da'wah education on TikTok has gained an extensive scope in the public view and the enthusiasm of the community to learn Islam or